(untitled) (Olhar de Professor, 2026)
This article emerges from a desire to share my experience and reflections arising from my perspective as a supervising professor in the interdisciplinary subproject Arts - Theater and Music, part of the Teacher Residency Program (RP). My aim is to highlight selected aspects of this trajectory, emphasizing significant moments experienced by the mentor teachers and the residents in the schools, who shared their experiences during training and evaluation meetings. The article is based on the participants’ reports, as well as on updated accounts from the now graduates of the Theater Licentiate program who took part in the RP. It also proposes to analyze the impact of an expanded pedagogical practice implemented in basic educational schools on teacher education in theatre. The reflections are grounded in authors such as Freire (1992), hooks (2013), Nóvoa (2022), Figueiredo (2023) and Santos (2008/2011).